(untitled) (International Journal of Biomedical Research, 2014)
Aim and objective: To study the demographic features of the patients suffering from the parotid tumors and the outcome of the parotid surgery. Study design : An observational and descriptive study. Place and duration of study : Department of General Surgery, K.IM.S, Andhra Pradesh, from Jan 2006 to November 2012. Material and methods : The study has been conducted at tertiary care teaching hospital in Andhra Pradesh from 2006 to 2012. The patients of both gender and all age groups who presented with parotid swellings were included in the study. The subjects were interviewed for history and then thorough clinical examination was carried out. They were subjected for routine and specialized investigations like FNAC, USG of parotid region and CT scan of parotid and neck. The patients were subjected to parotid surgery. Results : Out of 21 cases 10 were male and 11 female. Age range was from 11 to 65 year. All patients presented with unilateral parotid swelling. Fourteen cases (66.66 %) cases had pleomorphic adenoma and four cases had (19.04 %) malignanant tumor. Two cases had transient facial palsy whereas there were sialocoele, parotid fistula and postoperative hemorrhage one case of each. Conclusion : It is concluded that the parotid surgery can be safely performed in general surgery units with acceptable and comparable results.